Tirzepatide – a new hope for type 2 diabetes mellitus and obesity management. A literature review. - Stawicka, Izabela; Orzołek, Izabela; Jarmołowicz, Jakub; Boczar, Agata; Dryja, Patryk (Journal of Education, Health and Sport, 2024)
INTRODUCTION AND PURPOSE. While obesity and type 2 diabetes mellitus (T2DM) are defined (according to WHO) as civilization diseases we are still searching for the ideal tool to fight them. Recently, the Food and Drug Administration (FDA) and European Medicines Agency (EMA) approved tirzepatide subcutaneous injections as monotherapy or combination therapy, with diet and physical exercise, to achieve better glycemic blood levels in patients with diabetes and weight reduction among obese and overweighted patients. This review evaluates the efficacy and safety of using tirzepatide based on GIP/GLP-1 agonists clinical trials. MATERAILS AND METHODS. Literature available in the PubMeb Database and Google Scholar Databases was reviewed using keywords. RESULTS AND CONCLUSIONS. Tirzepatide is a novel medicine which stands against type 2 diabetes and obesity pandemic. Combining two agonists of GIP and GLP-1 receptors helps decrease glycemic blood levels, HbA1c levels and reducing body weight in more efficient way than the GLP-1 receptor agonists. All these effects have also resulted in minimizing cardiovascular risk which is observed as an improvement in heart failure, hyperlipidemia and hypertension. Beyond that, the recent data present possible positive long-term effect of tirzepatide in such diseases as MAFLD (metabolic associated fatty liver disease) and OSA (obstructive sleep apnea). However, triagonists, achieving a concurrent activation of GLP-1, GIP, and glucagon receptors, normalize body weight in a manner superior to that of monoagonists and dual agonists. Therefore, the triple agonism or other than GIP/GLP-1 combinations could soon represent a new standard for pharmaceutical interventions. KEYWORDS: tirzepatide; obesity; type 2 diabetes; weight reduction; GIP; GLP-1.